2018
DOI: 10.1093/molbev/msy136
|View full text |Cite
|
Sign up to set email alerts
|

Darwinian Positive Selection on the Pleiotropic Effects of KITLG Explain Skin Pigmentation and Winter Temperature Adaptation in Eurasians

Abstract: Human skin color diversity is considered an adaptation to environmental conditions such as UV radiation. Investigations into the genetic bases of such adaptation have identified a group of pigmentation genes contributing to skin color diversity in African and non-African populations. Here we present a population analysis of the pigmentation gene KITLG with previously reported signal of Darwinian positive selection in both European and East Asian populations. We demonstrated that there had been recurrent select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…Sulem et al (2007) found that a variant upstream of KITLG was associated with hair color in a genome-wide association scan in Icelanders and Dutch [46]. This variant likely lies in linkage disequilibrium, with an extended haplotype upstream of KITLG showing a strong signature of selection in humans [46][47][48]. Guenther et al (2014) found that this region drove expression exclusively in hair follicles using reporter constructs in mice [49].…”
Section: Discussionmentioning
confidence: 99%
“…Sulem et al (2007) found that a variant upstream of KITLG was associated with hair color in a genome-wide association scan in Icelanders and Dutch [46]. This variant likely lies in linkage disequilibrium, with an extended haplotype upstream of KITLG showing a strong signature of selection in humans [46][47][48]. Guenther et al (2014) found that this region drove expression exclusively in hair follicles using reporter constructs in mice [49].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the strongest signals are associated with genes previously involved in pigmentation, thermogenesis, and immune defense against pathogens ( Guenther et al. 2014 ; Yang et al. 2018 ), all of them phenotypes under strong selection in diverse human populations ( Karlsson et al.…”
Section: Discussionmentioning
confidence: 98%
“…Although rs12821256 is a causative variant of lighter hair color in northern Europeans ( Guenther et al. 2014 ), KITLG regulates the amount of melanin pigments in hair follicles as well as in the skin and is also involved in thermogenesis ( Yang et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, KITLG produces a protein involved in mast cell development, migration and function, and melanogenesis. KITLG has been documented as a target of evolution in recent studies and in humans it has been linked with thermoregulation (Yang et al 2018), which is a critical component of bat life history (Studier and O'Farrell 1972). In fact, upregulation of KITLG at low temperature helps promote the production of brown fat for heat generation (Huang et al 2014).…”
Section: Measures Of Heterozygosity Within Geographically and Temporamentioning
confidence: 99%